2011
DOI: 10.4236/ijcm.2011.22023
|View full text |Cite
|
Sign up to set email alerts
|

Syncope and Hypoglycemia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…Based on the data collected through the medical record from RSUD Dr. Soetomo Hospital Surabaya hospital about the sex and age group of the patient based in table 1 showed that the age group of patients was mostly over 65 years, as many as 39.8%. This result is in line with a previous study that described patients over 65 years of age who failed to experience autonomic neuroglycopenic and hypoglycemic symptoms because they have a slow response or awareness of hypoglycemic events (11) (12). In this study, females had a higher prevalence of 66,3%, which was in line with previous studies where the most sex group prevalence was female patients with hypoglycemia in T2DM was 57.44% (13).…”
Section: Discussionsupporting
confidence: 93%
“…Based on the data collected through the medical record from RSUD Dr. Soetomo Hospital Surabaya hospital about the sex and age group of the patient based in table 1 showed that the age group of patients was mostly over 65 years, as many as 39.8%. This result is in line with a previous study that described patients over 65 years of age who failed to experience autonomic neuroglycopenic and hypoglycemic symptoms because they have a slow response or awareness of hypoglycemic events (11) (12). In this study, females had a higher prevalence of 66,3%, which was in line with previous studies where the most sex group prevalence was female patients with hypoglycemia in T2DM was 57.44% (13).…”
Section: Discussionsupporting
confidence: 93%
“…This result was similar to the finding obtained by Lagi A. [21], who found that hypoglycemia syncope was unconscious and affected 1.9% of diabetic patients using insulin therapy. In addition, older diabetic patients exhibit a slower recovery from the transient loss of conscious, such as confusion, in the absence of autonomic manifestations, such as sweating.…”
Section: Discussionsupporting
confidence: 92%
“…The link between syncope and hypoglycaemia is controversial, although transient hypoglycaemia is classified among the causes of loss of consciousness . Recovery of consciousness is linked to spontaneous normalisation of glycaemia.…”
Section: Introductionmentioning
confidence: 99%